Antimicrobial Role of RNASET2 Protein During Innate Immune Response in the Medicinal Leech Hirudo verbana - Baranzini, Nicolò; De Vito, Annarosaria; Orlandi, Viviana Teresa; Reguzzoni, Marcella; Monti, Laura; de Eguileor, Magda; Rosini, Elena; Pollegioni, Loredano; Tettamanti, Gianluca; Acquati, Francesco; Grimaldi, Annalisa (Frontiers in Immunology, 2020)
The innate immune response represents a first-line defense against pathogen infection that has been widely conserved throughout evolution. Using the invertebrate Hirudo verbana (Annelida, Hirudinea) as an experimental model, we show here that the RNASET2 ribonuclease is directly involved in the immune response against Gram-positive bacteria. Injection of lipoteicoic acid (LTA), a key component of Gram-positive bacteria cell wall, into the leech body wall induced a massive migration of granulocytes and macrophages expressing TLR2 (the key receptor involved in the response to Gram-positive bacteria) towards the challenged inoculated. We hypothesized that the endogenous leech RNASET2 protein (HvRNASET2) might be involved in the antimicrobial response, as already described for other vertebrate ribonucleases, such as RNase3 and RNase7. In support of our hypothesis, HvRNASET2 was mainly localized in the granules of granulocytes and its release in the extracellular matrix triggered the recruitment of macrophages towards the area stimulated with LTA. The activity of HvRNASET2 was also evaluated on Staphylococcus aureus living cells by means of light, transmission and scanning electron microscopy analysis. HvRNASET2 injection triggered the formation of S. aureus clumps following a direct interaction with the bacterial cell wall, as demonstrated by immunogold assay. Taken together, our data support the notion that, during the early phase of leech immune response, granulocytes-released HvRNASET2 triggers bacterial clumps formation and, at the same time, actively recruits phagocytic macrophages in order to elicit a rapid and effective eradication of the infecting microorganisms from inoculated area.